PENINGKATAN HASIL BELAJAR BAHASA INGGRIS MATERI TEKS NARATIF SISWA SMK MELALUI PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Supadi Unipa (Program Studi Manajemen Pendidikan, 2019)
This article aims to describe: 1) student learning activities, 2) teacher teaching activities, 3) increasing of English learning outcomes was by using cooperative learning of jigsaw type. This class action research was conducted in 2 (two) cycles, with the research subject of accounting student of the grade X at SMK Pembangunan Jaya Jakarta which was registered in the even semester of school year 2018/2019, which amounted 42 students. This research object was the teachers teaching activities and students learning activities in English learning of narrative text materials. Data collection was obtained through twice of study observation and learning result was obtained through tests. The results showed that the cooperative learning of jigsaw types could significantly increase 1) Students learning activities were from an average of 3.2 in the first cycle to reach 3.82; 2) Teachers teaching activities were the average score of teacher teaching activity in the first cycle of 3.2 then in the second cycle reaches 3.91; and 3) students who mastered the first cycle as many as 24 students (57%) and did not master 18 students (43%) with an average score of 66, while on the second cycle increased 34 students (80%) who mastered and 8 students (20%) did not master with an average score of 76